Method for rapidly and efficiently removing and recycling polycyclic aromatic hydrocarbon in water body and carbon-based adsorbent
By using modified carbon-based adsorbent prepared by high-density activated carbon and H3PO4 or ZnCl2 activator, the problems of low removal efficiency and difficulty in desorption in the prior art are solved, and the rapid and efficient removal and recovery of PAHs in water bodies are achieved.
Patent Information
- Application Number
- CN202510149307.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as long adsorption time, low efficiency, difficulty in desorption and secondary pollution when removing polycyclic aromatic hydrocarbons (PAHs) in water bodies, and it is difficult to meet the needs of efficient industrial removal, enrichment and recycling.
By using high-density activated carbon as substrate and combining H3PO4 or ZnCl2 as activator, the activation process is controlled to obtain nano-micrometer multi-scale modified carbon-based adsorbent particles. The particles have a large number of interpenetrating long strip-shaped mesopories and a small number of irregular groove-shaped mesopories, which can quickly adsorb and resolve PAHs of different molecular weights.
It achieves rapid and efficient adsorption and desorption of polycyclic aromatic hydrocarbons, balances the adsorption and desorption efficiency, reduces the amount of adsorbent, and supports efficient recovery and reuse of PAHs.
Smart Images

Figure CN119608114A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano materials and environmental protection, and specifically relates to a method for quickly and efficiently removing polycyclic aromatic hydrocarbons in water and a carbon-based adsorbent. Background Art
[0002] Polycyclic aromatic hydrocarbons (PAHs) are a class of persistent organic pollutants that are widely present in the environment and are carcinogenic, teratogenic, and mutagenic. Many regulatory agencies, such as the U.S. Environmental Protection Agency and the Canadian Council of Ministers of the Environment, have listed 16 PAH compounds as priority pollutants in water and soil. According to relevant studies, it is expected that by 2030, the global release of PAHs into the environment will increase from 85 million tons in 2016 to 106.6 million tons, of which about 209,000 tons of PAHs will be released into the aquatic environment. The emission of large amounts of PAHs can cause serious environmental and health problems. Serious health hazards including acute toxicity, developmental toxicity, endocrine disruption, and even carcinogenicity have been confirmed by toxicological and epidemiological studies. Therefore, there is an urgent need to treat PAHs in environmental water bodies. Adsorption is considered to be the most promising treatment technology due to its simple operation, high cost-effectiveness, flexible operation, and low energy consumption. However, due to the hydrophobicity and large molecular size of aromatic hydrocarbons, the removal of multi-component aromatic hydrocarbons from wastewater by adsorption still faces great challenges. Therefore, it is urgent to find new materials that can effectively treat PAHs.
[0003] Carbon-based materials are considered the preferred adsorbents because of their low cost and ease of operation. Current carbon-based materials generally have problems with secondary pollution, long adsorption time and low removal efficiency, which seriously limit their application in actual production processes. In the prior art, the high-density activated carbon in industrial protective masks can provide effective protection for the wearer with its excellent filtering effect, strong adsorption capacity, good stability and reusability. At the same time, the combination of its main component carbon and other trace elements makes the activated carbon have a highly developed pore structure and a huge specific surface area in structure, thus having excellent adsorption performance. The main component of the high-density activated carbon in the industrial protective mask is carbon, and it also contains a small amount of oxygen, hydrogen, sulfur, nitrogen, chlorine and other elements. It is obtained by distilling and activating materials with high carbon content (such as wood, coal, fruit shells, bones, petroleum residues, etc.). These raw materials are specially treated to form a multi-pore structure of activated carbon, which gives it an extremely high specific surface area and adsorption capacity. See Attachment Fig.10, the surface of the high-density active material that has not been modified is relatively smooth. Generally, it is only prepared by high-temperature carbonization. Its volatile components will volatilize to form a pore structure, while the non-volatile components will continue to remain in the carbon material matrix, resulting in a large number of micropores with a size of 0-2 nm. However, the molecular size of most polycyclic aromatic hydrocarbon macromolecular pollutants is between 2-6 nm. It is difficult to rely on pore filling to remove such pollutants, resulting in poor adsorption and desorption effects. Therefore, more and more researchers optimize the surface structure of activated carbon to significantly improve the performance of the adsorbent. However, while the adsorption performance is improved, the desorption performance is often reduced, and the pollutants and adsorbents cannot be efficiently desorbed and recovered. For example, patent announcement CN117088367A discloses a method for preparing activated carbon for sewage by a variety of chemical modifications, wherein the activated carbon has a rich pore structure and a high specific surface area, and the adsorption performance is high while the analytical performance is sacrificed. Patent announcement CN118649660A discloses that the prepared adsorption material has a developed pore structure and a large specific surface area, and has a strong adsorption capacity for dissolved organic pollutants in water. However, during use, due to the complexity of the water body and the different physicochemical properties (hydrophilicity and hydrophobicity) of the pollutants, the adsorption capacity for the target pollutants decreases. The above-mentioned PAH treatment processes and materials in water bodies cannot fully consider the characteristics of PAH macromolecule size, hydrophobicity and polarity. There are problems such as the incoordination between the microstructure and physicochemical properties of the materials, long adsorption treatment time, low actual load, inability to take into account desorption and PAHs recovery, and the difficulty of adsorption materials being reused. These problems increase the cost and complexity of pollutant treatment and cannot meet the needs of efficient removal, enrichment, resource recovery and reuse of PAHs in industrial water bodies. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for quickly and efficiently removing polycyclic aromatic hydrocarbons in water and a carbon-based adsorbent. According to the characteristics of polycyclic aromatic hydrocarbons such as macromolecular size, hydrophobicity and polarity, a high-density activated carbon material is used as the substrate, and H 3 PO 4 or ZnCl 2Using activated carbon as an activator, by controlling the activated carbon substrate and the activation process, nano-micrometer-scale multi-scale modified carbon-based adsorbent particles are obtained, which are mainly composed of a large number of long strip-shaped mesopores that are interconnected and distributed in a nearly parallel direction, and supplemented by a small number of discrete irregular groove-shaped mesopores. The narrow long strip-shaped mesopores and irregular groove-shaped mesoporous structure of the particles cooperate with each other, and can quickly adsorb and decompose polycyclic aromatic hydrocarbons of different molecular weights (including large molecular weight), achieving a balance between adsorption and desorption performance and efficiency. On the one hand, it improves the adsorption and decomposition efficiency of pollutants, and on the other hand, it greatly reduces the amount of adsorbent used, which can meet the needs of efficient removal, enrichment, recovery and reuse of PAHs in industrial water bodies, and solve the above-mentioned technical problems.
[0005] The present invention provides the following technical solutions to achieve the above-mentioned purpose: A method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water, characterized in that it comprises the following steps: S1. Preparation of modified carbon-based adsorbent The pretreated high-density activated carbon is added to the activator solution, and the concentration, temperature, stirring speed and stirring time of the activator solution are synchronously controlled, and the activation is carried out by continuous magnetic stirring to obtain nano-micrometer-scale multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and supplemented by a small number of discrete irregular groove-shaped mesopores; the activator is H 3 PO 4 or ZnCl 2 ; S2. Treatment of wastewater polluted by polycyclic aromatic hydrocarbons The prepared modified carbon-based adsorbent (i.e., modified activated carbon adsorbent) particles are added to wastewater containing polycyclic aromatic hydrocarbons for adsorption treatment to fully enrich the polycyclic aromatic hydrocarbons in the water body; S3. Recovery of PAHs The modified carbon-based adsorbent enriched with polycyclic aromatic hydrocarbons is desorbed by dissolving, and then the solid-liquid separation is performed to recover the modified carbon-based adsorbent and the supernatant respectively; the recovered carbon-based adsorbent is washed and dried to restore the adsorption capacity; the supernatant is quickly concentrated to separate, purify and extract the polycyclic aromatic hydrocarbons.
[0006] The step S1 specifically includes the following steps: S1-1 The original high-density activated carbon is washed with deionized water to remove surface impurities; then, it is dried in a drying device to obtain pretreated high-density activated carbon; S1-2 According to H 3 PO 4 The mass ratio (dry matter) of pretreated high-density activated carbon is 1: (5~10), or ZnCl 2The pretreated high-density activated carbon is added to a solution of 0.1-0.2 mol / L prepared by the above activator at a mass ratio of 1: (3.5-7) to the pretreated high-density activated carbon (dry matter), and activated by magnetic stirring at a temperature of 25-40°C and a speed of 450-550 rpm for 10-14 h, so that the activator reacts with the carbon matrix in the activated carbon to remove insoluble impurities and change the microscopic surface morphology and physicochemical properties of the activated carbon, thereby obtaining nano-micron multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and a small number of discrete irregular groove-shaped mesopores as auxiliary, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5-4.5 μm; S1-3: washing the adsorbent material activated in step S1-2 with deionized water until the pH of the rinse solution is approximately neutral, and collecting the activated modified carbon-based adsorbent particles (modified activated carbon particles) by centrifugation; S1-4 The modified carbon-based adsorbent particles obtained in step S1-3 are placed in a vacuum drying oven for drying, cooled to room temperature, collected and placed in a glass desiccator for standby use, to obtain a modified carbon-based adsorbent.
[0007] A modified carbon-based adsorbent is used to implement the aforementioned method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water bodies. It is a surface-modified solid particle material obtained by controlled activation with high-density activated carbon as a substrate and synchronously controlling the activation reaction conditions of an activator. The surface of the modified carbon-based adsorbent has a nano-micrometer multi-scale microstructure, which is mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in nearly parallel directions, and a small number of discrete irregular groove-shaped mesopores as a supplement. The slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5 to 4.5 μm, so that polycyclic aromatic hydrocarbons of different molecular weights can be rapidly adsorbed and analyzed, and it is particularly suitable for rapid adsorption and analysis of large-sized (large molecular weight) polycyclic aromatic hydrocarbons and other organic pollutants.
[0008] Compared with the prior art, the present invention has the following advantages and effects: 1. This invention takes high-density activated carbon as the substrate and H 3 PO 4 、ZnCl 2Using activated carbon as an activator, by synchronously controlling the activated carbon substrate and the activation process, nano-micrometer-scale multi-scale modified carbon-based adsorbent particles are obtained, which are mainly composed of a large number of long strip-shaped mesopores that are interconnected and distributed in a nearly parallel direction, and supplemented by a small number of discrete irregular groove-shaped mesopores. The narrow long strip-shaped mesopores (gullies) and irregular groove-shaped mesopores (grooves) structures of the particles cooperate with each other, can quickly adsorb and decompose large-sized polycyclic aromatic hydrocarbons, and can achieve a balance between adsorption and desorption efficiency, thereby increasing the actual adsorption load; on the one hand, it improves the adsorption and decomposition efficiency of pollutants, and on the other hand, it greatly reduces the amount of adsorbent used.
[0009] 2. The preparation method of the carbon-based adsorbent provided by the present invention is simple, and the specific reaction conditions of activation are easy to achieve synchronous control. After controlled activation, the microstructure and physical and chemical properties of the adsorbent undergo essential changes: the mesoporosity of the activated carbon can reach 54.20%. Since the molecular size (diameter) of most polycyclic aromatic hydrocarbons (including other natural macromolecules) is 2-6 nm, it is very suitable for the adsorption and analysis of organic substances such as PAHs of different molecular weights. In addition, through H 3 PO 4 and ZnCl 2 The controlled activation of the activator can stably produce a large number of mutually interconnected strip-shaped grooves and spherical groove mesoporous structures, and the generated grooves and groove mesopores are also mutually interconnected. The gully gap width or groove diameter size is mainly distributed in the range of 1.75~4.27 μm, and the distribution is relatively loose. The gullies are spaced and nearly parallel, which can efficiently and massively adsorb pollutants of different molecular weights; at the same time, the high delocalization of the gully and groove mesoporous structure can also enhance the π-π interaction, making it easy for hydrophobic PAHs and other pollutants to adhere to the adsorbent material; after activation, the C element content of the adsorbent is reduced and the O element content is increased. FTIR test shows that the activated carbon surface of the adsorbent is rich in oxygen functional groups, which can indirectly promote the rapid enrichment of pollutants on the surface. The present invention utilizes a controlled activation process to obtain a large number of narrow and nearly parallel grooves and grooves on the surface of the adsorbent material. The mesoporous structure balances the efficiency of adsorption and desorption, so that the adsorbent can accelerate the adsorption of pollutants, increase the load, and reduce the amount of adsorbent on the one hand, and can also achieve rapid desorption, separation and recovery of PAHs on the adsorbent on the other hand. It is of great significance for industrialized and large-scale treatment of wastewater from coal chemical or petroleum and coking enterprises, and realizing the synchronous resource utilization of polluted water and PAHs.
[0010] 3. The modified carbon-based adsorbent (modified activated carbon adsorbent) prepared by the present invention has easy-to-obtain base materials and activators, fewer overall steps, simple processes, easy-to-control reaction conditions, stable product quality, and easy industrial production. Through actual testing, it was found that by adding a small proportion of modified carbon-based adsorbent, the removal rate of naphthalene, phenanthrene and pyrene by the modified carbon-based adsorbent can reach more than 90% within 30 minutes, and the maximum adsorption capacity can reach 199.9 mg / g, far exceeding the existing similar materials. It can be widely used to treat wastewater contaminated with PAHs of different molecular weights such as naphthalene, phenanthrene and pyrene, and of course it can also be used to treat other organic pollutants in water bodies.
[0011] 4. The modified carbon-based adsorbent material prepared by the present invention has a good effect on organic pollutants of different molecular weights and hydrophilicity such as naphthalene, phenanthrene and pyrene. On the one hand, the presence of a large number of gully-groove mesoporous through-structures is conducive to the rapid transfer of macromolecular PAHs in the pores, thereby penetrating into the internal microporous structure of the adsorbent, and can play a good role in pore filling to adsorb PAHs; on the other hand, the rich and rough microstructure on the surface of the adsorbent and the synergistic coordination of functional groups are conducive to chemical adsorption or adsorption of PAHs through π-π interactions, so that PAHs can be quickly separated from the water body. For the modified carbon-based adsorbent material that reaches a high load after adsorption, it can be further dissolved in methanol / acetonitrile after collection, and the extract can be concentrated by rotary evaporation and other methods to separate the solid and liquid, and the solid adsorbent particles and liquid PAHs can be recovered separately. The recovery process is efficient and fast; whether it is the adsorption process or the desorption process, compared with similar materials provided by the prior art, it can significantly reduce the amount of adsorbent, speed up the processing speed, and avoid secondary pollution during adsorption and analysis.
[0012] 5. The method and material provided by the present invention focus on obtaining unique microstructures and physical and chemical properties through controlled activation and modification of high-density activated carbon materials to balance the adsorption and desorption efficiency and loading capacity. Specifically, in the activation and modification process, a large number of long strip-shaped mesoporous cracks and irregular groove mesopores with nearly parallel distribution and high delocalization are obtained on the surface of the activated carbon material through the physical-chemical composite effect, and the O element content is increased. The two cooperate with each other to enhance the affinity of the activated carbon surface. On the one hand, it can efficiently enrich PAHs in wastewater, and on the other hand, it can reduce the fixation of PAHs adsorbed to the inside of the adsorbent, which is conducive to subsequent efficient desorption and recovery.
[0013] 6. The treatment method and special adsorbent material provided by the present invention are combined with each other to establish a new, full-process PAHs wastewater or other large molecular size pollutant wastewater treatment and resource recovery method, which greatly simplifies the modification and preparation process of the adsorbent material and the steps of pollutant adsorption and recovery. On the one hand, it can improve the PAHs removal rate and removal efficiency in the water body, and at the same time improve the recovery rate and recovery efficiency of PAHs and the adsorbent itself, which is conducive to industrial application and obtains better industrial sewage treatment and resource recovery effects.
[0014] 7. The treatment method and adsorbent material provided by the present invention have the advantages of easy material preparation, low cost, high adsorption rate, good recovery effect, etc., and can take into account the efficiency of adsorption and analysis. It has broad application prospects in the field of PAHs wastewater and other industrial wastewater treatment. At the same time, the present invention can also be extended to the treatment of wastewater containing other large molecular organic pollutants, so as to realize the more universal application of the modified carbon-based adsorbent for the adsorption and analysis of more large molecular pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Schematic diagram of the preparation process of the modified carbon-based adsorbent material in an embodiment of the present invention; Figure 2 In the embodiment of the present invention, H 3 PO 4 SEM image of the modified carbon-based adsorbent obtained after activation for 12 h; Figure 3 H in the embodiment of the present invention 3 PO 4 Schematic diagram of the mesopore size (pore diameter) distribution of the modified carbon-based adsorbent obtained after activation for 12 h; Figure 4 is H in the comparative example of the present invention 3 PO 4 SEM image of the modified carbon-based adsorbent obtained after activation for 6 h; Figure 5 is H in the comparative example of the present invention 3 PO 4 SEM image of the modified carbon-based adsorbent obtained after activation for 24 h; Figure 6 In the embodiment of the present invention, ZnCl 2 SEM image of activated carbon adsorbent after 12 h of activation; Figure 7 In the embodiment of the present invention, ZnCl 2 Schematic diagram of mesopore size distribution of activated carbon adsorbent and microstructure size distribution diagram 12h after activation; Figure 8 The present invention compares ZnCl 2SEM image of activated carbon adsorbent after 6 h of activation; Fig. 9 It is ZnCl in the comparative example of the present invention. 2 SEM image of activated carbon adsorbent after 24h activation; Fig.10 is a SEM image of an unmodified activated carbon substrate in a comparative example of the present invention; Fig.11 1 is a schematic diagram of nitrogen adsorption-desorption curves-specific surface areas of different adsorbent materials of the present invention; Fig.12 Schematic diagram of nitrogen adsorption-desorption curves-pore volumes of different adsorbent materials of the present invention; Fig.13 is a curve showing the change of the adsorption capacity of naphthalene pollutants by different adsorbent materials of the present invention over time; Fig.14 is a curve showing the change of the adsorption capacity of phenanthrene by different adsorbent materials of the present invention over time; Fig.15 is a curve showing the change of the adsorption capacity of different adsorbent materials of the present invention for pyrene pollutants over time; Fig.16 is the infrared spectra of different adsorption materials of the present invention before adsorption; Fig.17 is an infrared spectrogram of naphthalene adsorbed by different adsorbent materials of the present invention; Fig.18 is an infrared spectrum of phenanthrene adsorbed on different adsorption materials of the present invention; Fig.19 It is the infrared spectra of different adsorption materials of the present invention after adsorbing pyrene. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0017] Basic Example A method for rapidly and efficiently removing and recovering polycyclic aromatic hydrocarbons in water comprises the following steps: S1. Preparation of modified carbon-based adsorbent See attached Figure 1The pretreated high-density activated carbon material is added to the activator solution, and the concentration, temperature, stirring speed and stirring time of the activator solution are synchronously controlled. The activation is carried out by continuous magnetic stirring to obtain nano-micrometer-scale multi-scale modified carbon-based adsorbent particles, which are mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and supplemented by a small number of discrete irregular groove-shaped mesopores; the activator is H 3 PO 4 or ZnCl 2 , specifically: S1-1 The original high-density activated carbon granular material is washed with deionized water to remove surface impurities; then, it is placed in a drying device for drying to obtain pretreated high-density activated carbon; the original high-density activated carbon granular material in this embodiment is a high-density activated carbon solid granular material taken out from a commercially available industrial air filter protective mask. The SEM image of the original material is as shown in FIG. Fig.10 As shown, the surface is smooth, the internal pores are few, the diameter of the grooves is mainly distributed above 20μm, and there are no interpenetrating gullies and smaller-scale grooves; S1-2 synchronously controls the concentration, temperature, stirring speed and stirring time of the activator solution as follows: 3 PO 4 The mass ratio (dry matter) of pretreated high-density activated carbon is 1: (5~10), or ZnCl 2 The pretreated high-density activated carbon is added to a solution of 0.1-0.2 mol / L prepared by the above activator at a mass ratio of 1: (3.5-7) to the pretreated high-density activated carbon (dry matter), and activated by magnetic stirring at a temperature of 25-40°C and a speed of 450-550 rpm for 10-14 h, so that the activator reacts with the carbon matrix in the activated carbon to remove insoluble impurities and change the microscopic surface morphology and physicochemical properties of the activated carbon, thereby obtaining nano-micron multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and a small number of discrete irregular groove-shaped mesopores as auxiliary, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5-4.5 μm; S1-3: The modified carbon-based adsorbent particles activated in step S1-2 are then washed with deionized water until the pH of the rinse liquid is approximately neutral, and the modified activated carbon particles after activation are collected by centrifugation; the activated solid particle material is washed with deionized water and then dried to obtain a modified carbon-based adsorbent powder material; the surface of the prepared carbon-based adsorbent material becomes rough, presenting a gully-like, wrinkled and groove structure, with a relatively loose distribution, and more adsorption sites are available; the activated carbon-based adsorbent material has a higher specific surface area, more adsorption sites, and a high delocalization performance of the groove structure, has a better affinity for polycyclic aromatic hydrocarbons, and can quickly enrich PAHs in water through π-π; S1-4 The modified carbon-based adsorbent particles obtained in step S1-3 are placed in a vacuum drying oven for drying, cooled to room temperature, collected and placed in a glass desiccator for standby use, to obtain a modified carbon-based adsorbent.
[0018] In this step, the activator can react with the high-density activated carbon substrate under stirring to accelerate the decomposition of organic matter in the substrate, such as α-O-4 and β-O-4, which have low energy barriers. As the activation proceeds, small molecules are slowly eliminated, resulting in spatial defects and residual pores to generate a large number of long strips of mesopores that are interconnected, and a large number of micron-sized groove structures that are irregularly distributed around each mesopore, connected to the mesopores and diffused outward; In this step, by controlling the activation time within the range of 10 to 14 hours and maintaining other identical activation conditions, the gap height of the long strip mesopores (grooves) and the diameter of each groove-shaped mesopore can be mainly distributed within the range of 1.5 to 4.5 μm during the activation process, and the microscopic surface morphology and physicochemical properties of the obtained modified carbon-based adsorbent particles are also highly similar, and the adsorption and desorption performances are also similar; however, if this time range is exceeded, materials with similar microscopic surface morphology and physicochemical properties cannot be obtained, and the technical effects of the present invention cannot be achieved.
[0019] The embodiment of the present invention can obtain a large number of mutually interpenetrating long strip mesopores with a nearly parallel distribution by synchronously controlling the concentration, temperature, stirring speed and activation time of the activator, and control the direction and main scale distribution range of the mesopores within the range of 1.5~4.5μm, so as to take into account efficient adsorption and desorption. When the activator reacts with the activated carbon substrate, the decomposition of organic matter in the activated carbon can be accelerated; and with the increase of the concentration of the activator or the increase of the activation time, the amount of small molecules eliminated is more, resulting in spatial loss and pore residues, generating a large number of mutually interpenetrating long strip mesopores with a nearly parallel distribution of the gap direction, and around the long strip mesopores, there are a small number of irregular groove-shaped mesopores distributed, and the two cooperate with each other, through a large number of cracks + grooves with a size in the range of 1.5~4.5 μm, with a high specific surface area. The composite structure has a good affinity for polycyclic aromatic hydrocarbons, can quickly enrich PAHs in water, and can also quickly desorb.
[0020] S2. Treatment of wastewater polluted by polycyclic aromatic hydrocarbons The prepared modified carbon-based adsorbent (i.e., modified activated carbon adsorbent) particles are added to wastewater containing polycyclic aromatic hydrocarbons for adsorption treatment to fully enrich the polycyclic aromatic hydrocarbons in the water body; specifically: S2-1: Detection of concentration of PAHs in water; S2-2: Calculate the required amount of carbon-based adsorbent; S2-3: Add carbon-based adsorbent to wastewater, stir, and take samples at specific time intervals; S2-4: Detect the residual concentration of PAHs in the treated water. If it is not reached, continue stirring and treating until it meets the set discharge standard; S3. Recovery of PAHs The modified carbon-based adsorbent enriched with polycyclic aromatic hydrocarbons is desorbed by dissolving, and then the solid-liquid separation is performed to recover the modified carbon-based adsorbent and the supernatant respectively; the recovered carbon-based adsorbent is washed and dried to restore the adsorption capacity; the supernatant is quickly concentrated, separated, purified, and polycyclic aromatic hydrocarbons are extracted. Specifically: S3-1: Desorbing the modified carbon-based adsorbent enriched with polycyclic aromatic hydrocarbons by dissolving it in methanol or acetonitrile, followed by solid-liquid separation, and recovering the modified carbon-based adsorbent and the supernatant respectively; S3-2: Wash and dry the recovered carbon-based adsorbent to restore its adsorption capacity for the next adsorption; S3-3: Use extraction, rotary evaporation or nitrogen blowing to quickly concentrate the supernatant, separate, purify and extract polycyclic aromatic hydrocarbons.
[0021] A modified carbon-based adsorbent is used to implement a method for rapidly and efficiently removing and recovering polycyclic aromatic hydrocarbons in water. It is a surface-modified solid particle material obtained by controlled activation using high-density activated carbon as a substrate and synchronously controlling the activation reaction conditions of an activator.
[0022] The modified carbon-based adsorbent provided in this embodiment is based on the porous structure of the high-density activated carbon material itself, and then the surface is modified by the activator, so that the surface of the modified carbon-based adsorbent forms a nano-micron multi-scale microstructure with a large number of interpenetrating, parallel-distributed long strip-shaped slit mesopores as the main part, and a small number of discrete irregular groove-shaped mesopores as the auxiliary part, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5~4.5μm, which can quickly adsorb and analyze polycyclic aromatic hydrocarbons of different molecular weights. Based on its microstructural characteristics (containing dispersed gullies and groove structures mainly distributed in the scale of 1.5~4.5 μm), and the surface contains rich surface functional groups and high mesoporosity and other physical and chemical properties, on the one hand, it can quickly and efficiently remove and recover polycyclic aromatic hydrocarbons in water, and at the same time, it can also quickly recover and regenerate the modified carbon-based adsorbent itself.
[0023] The activator is H 3 PO 4 or ZnCl 2 ; Synchronously control the activation reaction conditions of the activator, including synchronously controlling the concentration, temperature, stirring speed and stirring time of the activator solution, specifically: the concentration of the activator solution is 0.1~0.2mol / L, the reaction temperature is 25~40℃, the magnetic stirring speed is 450~550 rpm, and the stirring duration is 10~14 h.
[0024] The present embodiment provides a method for rapid and efficient removal and recovery of PAHs in water and a carbon-based adsorbent. The modified carbon-based adsorbent is specially prepared for PAHs and has a large number of interconnected long strip-shaped grooves and groove structures. The pore sizes of the optimized grooves and grooves are mainly distributed in the range of 1.75 to 4.27 μm. The size distribution is relatively loose, and the specific surface area is relatively high. It has good affinity for PAHs of different molecular weights, can quickly enrich PAHs in water, and can further quickly desorb.
[0025] The modified carbon-based adsorbent provided by the embodiment of the present invention has a unique microstructure. After the high-density activated carbon substrate is activated, it is rich in oxygen-containing functional groups and has a large number of strip-shaped distributions, interconnected crack mesoporous structures and surface groove structures; at the same time, the original smooth activated carbon surface becomes significantly rough, and numerous narrow strip-shaped elongated gullies and groove structures are presented on the surface and inside. The gullies are almost parallel to each other, and the multi-layer folds formed together with the irregular grooves are unevenly distributed, which can expand the pores and significantly increase the sites available for adsorption, and they are interconnected; at the same time, the high delocalization of the narrow and long gullies and groove structures is conducive to improving the adhesion of PAHs and the like on the adsorbent material through π-π interactions, and promoting the rapid enrichment of pollutants on the surface. After actual testing, the removal rate of naphthalene, phenanthrene and pyrene by the modified carbon-based adsorbent can quickly reach more than 90%, the maximum adsorption capacity can reach 199.9 mg / g, and the pore size distribution range is large, so it can be used to treat wastewater containing naphthalene, phenanthrene and pyrene with different molecular weights; based on the above unique microstructure and physicochemical properties, the carbon-based adsorbent can be further dissolved in methanol / acetonitrile after adsorption, and the PAHs can be recovered after rapid concentration and purification.
[0026] The modified carbon-based adsorbent provided in the embodiment of the present invention has a wide range of material sources, a simple preparation process, a low preparation cost, high adsorption / desorption efficiency, a large adsorption capacity, and is reusable. It can reduce the amount of adsorbent used overall and avoid secondary pollution during use.
[0027] The following is combined with Figures 1 to 19 The present invention is described in detail with reference to a plurality of embodiments and comparative examples.
[0028] In Examples 1 to 3, as well as Comparative Examples 1 and 2, H 3 PO 4 They are activators, and the difference lies in the different process conditions used in the activation process.
[0029] Example 1 This embodiment is based on the above basic embodiment. 3 PO 4 The activated carbon was activated for 12 hours to prepare a modified carbon-based adsorbent which has enhanced surface affinity of activated carbon and takes into account adsorption and desorption efficiency, and then applied to the adsorption and recovery of naphthalene in water.
[0030] First, a modified carbon-based adsorbent is prepared, comprising the following steps: (1) The commercially available high-density activated carbon solid particle material was used as the substrate, and was first washed with deionized water for 3 times to remove surface impurities. Subsequently, it was placed in a drying device (oven) and dried at 60°C for 12 h to make the moisture content ≤3%. After cooling to room temperature, it was collected and placed in a dryer to obtain a pretreated high-density activated carbon material, which was then sealed for later use; (2) Weigh 5 g of pretreated high-density activated carbon material and prepare the corresponding mass of H 3 PO 4 And the concentration is 0.1 mol / L H 3 PO 4 Solution; heating H 3 PO 4 The solution was heated to 30°C, and then the pretreated high-density activated carbon was added to the H 3 PO 4 The solution was kept at a temperature of 30°C and magnetically stirred at a speed of 500 rpm for 12 h for activation; during the activation process, the activator was stirred at a uniform speed to react with the carbon matrix in the activated carbon, remove the insoluble impurities and change the microscopic surface morphology and physical and chemical properties of the activated carbon, and obtain nano-micron multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and a small number of discrete irregular groove-shaped mesopores as auxiliary, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.75-4.27 μm; (3) washing the modified carbon-based adsorbent particle material activated in step (2) with deionized water until the pH of the rinse solution is approximately neutral, and collecting the obtained modified carbon-based adsorbent particles by centrifugation; (4) The modified carbon-based adsorbent particles obtained in step (3) are placed in a vacuum drying oven and dried at 60° C. for 12 h. After cooling to room temperature, the particles are collected and sealed in a desiccator to obtain a modified carbon-based adsorbent (hereinafter referred to as adsorbent).
[0031] The prepared modified carbon-based adsorbent (modified activated carbon particles) is then subjected to material characterization, including the following steps: Field emission scanning electron microscopy (SEM, Gemini SEM 500) was used to analyze the surface morphology of the adsorbed materials. A multi-station extended automatic rapid surface area analyzer (Micromeritics ASAP 2020) was used to analyze the surface morphology of the adsorbed materials at 77 K. 2 BET (Bet-E) was used to characterize the total surface area, total pore volume, and micropore volume of the material; Fourier transform infrared spectroscopy (FTIR) was used to test the surface functional groups.
[0032] Figure 2~Figure 5 H3 PO 4 SEM images of carbon-based adsorbents after continuous activation at different modification times. Figure 2 It can be seen that after H 3 PO 4 After activation, the surface of the adsorbent became rough. After 12 hours of activation, a mesoporous structure with interlaced grooves and gullies appeared, and the width of the mesopores was mainly concentrated in the range of 1.75-4.27 μm ( Figure 3 As shown in Figure 2), the distribution is relatively loose. Fig.10 , its microscopic morphology has undergone essential changes.
[0033] Table 1 shows the element proportions and pore structure parameters of different adsorbents in the modified carbon-based adsorbent prepared in this embodiment. 3 PO 4 The proportions of the elements C, N and O in the activated adsorbent changed significantly. Compared with the original high-density activated carbon, the proportion of the C element in the activated adsorbent decreased, while the proportion of the O element increased, indicating that the C element participated in the reaction during the activation process, resulting in a decrease in the content of the element, while the oxidation reaction caused the O element content to increase.
[0034] It can also be seen from Table 1 that the present invention uses H 3 PO 4 The total specific surface area, total pore volume and microporosity of different adsorbent materials obtained by solution activation. Among them, AC represents pretreated high-density activated carbon, HAC represents Example 1 after H 3 PO 4 The activated modified carbon-based adsorbent, ZAC, represents Example 4 after ZnCl 2 Modified carbon-based adsorbent after activation.
[0035] It can be seen from Table 1 that compared with the pretreated high-density activated carbon material (AC), the specific surface area, total pore volume, mesopore ratio and average pore size of the modified carbon-based adsorbent after activation are increased. 3 PO 4 and ZnCl 2 The specific surface area after activation increased by 60.35% and 63.91%; at the same time, the total pore volume in the adsorbent also increased by 67.95% and 54.13%, the average pore size increased by 3.4% and 0.3%, and the H 3 PO 4 The proportion of activated mesopores increased by 21.6%, indicating that the controlled activation process allowed the activator and the carbon matrix to react, increasing the surface and internal pore structure of the original activated carbon material, resulting in the appearance of more grooves and recesses on the surface and inside that are suitable for the adsorption of PAHs.
[0036] also, Fig.16 Including this embodiment H 3 PO 4 FTIR spectrum of the activated modified carbon-based adsorbent. The peaks at wavelengths of 3752, 2338, 1765, 1517, 1130 and 1012 cm-1 correspond to OH, C=C bond, carboxyl O=CO bond, benzene ring C=C stretching vibration, CH in-plane bending vibration and alkoxy CO, respectively. Compared with the unmodified activated carbon, the peaks at 3752 and 3615 cm-1 -1 The -OH stretching vibration intensity at 1545 cm -1 It is the C=C stretching vibration of the benzene ring in the carbon-based adsorbent material.
[0037] Table 1
[0038] Finally, this embodiment H 3 PO 4 The modified carbon-based adsorbent prepared by activation is applied to the adsorption and recovery of naphthalene in water, comprising the following steps: Adsorption treatment process: Weigh 3 groups of 5 mg of modified carbon-based adsorbent material prepared under the activation conditions of this embodiment, add it to 200 mL of pre-prepared wastewater containing naphthalene pollutants, seal it with a sealing film, and place it in a water bath shaker. The parameters of the shaker are set to 130 rpm and the temperature is 30°C. Take 1 mL of supernatant sample at specific time intervals and filter it with a 0.22μm microporous filter membrane. A Shimadzu LC-20AT high performance liquid chromatograph (HPLC) and a C18 reverse chromatographic column are used as the separation column. The mobile phase is methanol: water (95:5), the injection volume is 20 μL, the retention time is 15 min, the temperature is 30°C, and the flow rate is 1 mL / min for detection. The wavelength of the instrument detector of naphthalene is set to 228 nm.
[0039] like Fig.13 As shown in the figure, the adsorption amount gradually increases with time. In 200 mL of naphthalene solution with an initial concentration of 30 mg / L within 30 min, the adsorption capacity of the adsorbent reaches equilibrium. 3 PO 4 The activated adsorbent material reached equilibrium within 5 minutes and had a high adsorption capacity. 3 PO 4 The naphthalene removal rate of activated carbon is about 98.12%, and the equilibrium adsorption capacity is about 99.9 mg / g.
[0040] Fig.17This is the FTIR of the modified carbon-based adsorbent of this example after adsorption of naphthalene. As shown in the figure, at 2930, 2354 and 1504 cm -1 The peak intensity at corresponds to the stretching vibration of -OH and CH after adsorption of pollutants. Compared with the standard FTIR spectrum of naphthalene in the ChemSider database, it is found that the standard spectrum can correspond to the enhanced peaks of specific wavelengths on the adsorbent, which can provide evidence for the presence of naphthalene on the adsorbent. After adsorption, the peaks corresponding to the skeleton vibration of the C=C bond moved from 2338 to 2354 cm -1 , which confirms that π-π interaction plays an important role in the adsorption process between the adsorbent and PAHs.
[0041] Desorption process: freeze-dry the modified carbon-based adsorbent used for adsorbing naphthalene at -80 ° C, soak it in 10 mL of methanol and place it in a shaker for 2 h; then separate the solid and liquid, wash the recovered modified carbon-based adsorbent particles with water, dry them, and use them for adsorption again; concentrate the washed methanol with nitrogen, and then separate it, so as to maintain a high naphthalene recovery rate. Through testing, the modified carbon-based adsorbent recovered after one adsorption in this embodiment can still maintain an adsorption efficiency and loading capacity of more than 80% when it is used for re-adsorption of naphthalene pollutants again.
[0042] Example 2 This embodiment is based on the above embodiment 1. 3 PO 4 As an activator, a modified carbon-based adsorbent is prepared to enhance the surface affinity of activated carbon and take into account the adsorption and desorption efficiency. The modified carbon-based adsorbent is basically the same as Example 1, except that: The modified carbon-based adsorbent is prepared, comprising the following steps: (1) The commercially available high-density activated carbon solid particle material was used as the substrate, and was first washed with deionized water for 3 times to remove surface impurities. Subsequently, it was placed in a drying device (oven) and dried at 60°C for 10 h to make the moisture content ≤3%. After cooling to room temperature, it was collected and placed in a dryer to obtain a pretreated high-density activated carbon material, which was then sealed for later use; (2) Weigh 5 g of pretreated high-density activated carbon material and prepare the corresponding mass of H 3 PO 4 And the concentration is 0.2 mol / L H 3 PO 4 Solution; heating H 3 PO 4 The solution was heated to 40°C, and the pretreated high-density activated carbon was added to the H 3 PO 4The solution is kept at a temperature of 40°C and magnetically stirred at a speed of 550 rpm for 10 hours for activation; during the activation process, the activator is stirred at a uniform speed to react with the carbon matrix in the activated carbon, remove the insoluble impurities and change the microscopic surface morphology and physical and chemical properties of the activated carbon, and obtain nano-micron multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and a small number of discrete irregular groove-shaped mesopores as auxiliary, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5-4.5 μm; (3) washing the modified carbon-based adsorbent particle material activated in step (2) with deionized water until the pH of the rinse solution is approximately neutral, and collecting the obtained modified carbon-based adsorbent particles by centrifugation; (4) The modified carbon-based adsorbent particles obtained in step (3) are placed in a vacuum drying oven and dried at 100° C. for 10 h. After cooling to room temperature, the particles are collected and sealed in a desiccator to obtain a modified carbon-based adsorbent.
[0043] Then, the prepared modified carbon-based adsorbent was characterized. Its microstructure, morphology, physicochemical properties, etc. are basically the same as those of the modified carbon-based adsorbent prepared in Example 1, so it will not be described again.
[0044] Finally, the modified carbon-based adsorbent prepared in this embodiment is applied to the adsorption and recovery of phenanthrene in water, comprising the following steps: (5) If Fig.14 As shown in the figure, the adsorption amount of phenanthrene gradually increases with time. In 200 mL of phenanthrene solution with an initial concentration of 1 mg / L within 30 min, the adsorption capacity of the adsorbent reaches equilibrium. 3 PO 4 The activated adsorbent material reached equilibrium within 10 min and had a high adsorption capacity. 3 PO 4 The activated carbon has a phenanthrene removal rate of about 98.73%, and the equilibrium adsorption capacity is about 9.422 mg / g. Fig.18 FTIR of the adsorbent activated by H3PO4 after adsorption of phenanthrene. As shown in the figure, the peaks at 3443, 2362, 1604 and 1367 cm -1 A new peak with a stronger peak intensity appears at the adsorbent. Compared with the standard FTIR spectrum of phenanthrene in the ChemSider database, it is found that the standard spectrum can correspond to the enhanced peak of a specific wavelength on the adsorbent, which can provide evidence for the presence of phenanthrene on the adsorbent.
[0045] (6) Recover the adsorbent after adsorption equilibrium. The adsorbent used for adsorption of the phenanthrene solution was freeze-dried at -80 °C, soaked in 10 mL of methanol and placed in a shaker for 2 h. The solid-liquid separation was then carried out, and the recovered adsorbent was washed with water and dried for re-adsorption. The recovered adsorbent was used for re-adsorption of phenanthrene pollutants, and the adsorption efficiency was maintained above 75%. The washed methanol was concentrated by nitrogen blowing and then separated to maintain a good phenanthrene recovery rate.
[0046] Example 3 This embodiment is based on the above embodiment 1. 3 PO 4 As an activator, a modified carbon-based adsorbent is prepared to enhance the surface affinity of activated carbon and take into account the adsorption and desorption efficiency. The modified carbon-based adsorbent is basically the same as Example 1, except that: The modified carbon-based adsorbent is prepared, comprising the following steps: (1) The commercially available high-density activated carbon solid particle material was used as the substrate, and was first washed with deionized water for 3 times to remove surface impurities. Subsequently, it was placed in a drying device (oven) and dried at 60°C for 10 h to make the moisture content ≤3%. After cooling to room temperature, it was collected and placed in a dryer to obtain a pretreated high-density activated carbon material, which was then sealed for later use; (2) Weigh 5 g of pretreated high-density activated carbon material and prepare the corresponding mass of H 3 PO 4 The concentration of H was 0.15 mol / L. 3 PO 4 Solution; heating H 3 PO 4 The solution was heated to 25°C, and then the pretreated high-density activated carbon was added to the H 3 PO 4 The solution is kept at a temperature of 25°C and magnetically stirred at a speed of 450 rpm for 14 hours for activation; during the activation process, the activator is stirred at a uniform speed to react with the carbon matrix in the activated carbon, remove the insoluble impurities and change the microscopic surface morphology and physical and chemical properties of the activated carbon, and obtain nano-micron multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and a small number of discrete irregular groove-shaped mesopores as auxiliary, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5-4.5 μm; (3) washing the modified carbon-based adsorbent particle material activated in step (2) with deionized water until the pH of the rinse solution is approximately neutral, and collecting the obtained modified carbon-based adsorbent particles by centrifugation; (4) The modified carbon-based adsorbent particles obtained in step (3) are placed in a vacuum drying oven and dried at 60° C. for 12 h. After cooling to room temperature, the particles are collected and sealed in a desiccator to obtain a modified carbon-based adsorbent.
[0047] Then, the prepared modified carbon-based adsorbent was characterized. Its microstructure, morphology, physicochemical properties, etc. are basically the same as those of the modified carbon-based adsorbent prepared in Example 1, so it will not be described again.
[0048] Finally, the modified carbon-based adsorbent (abbreviated as adsorbent) prepared in this embodiment is applied to the adsorption and recovery of pyrene in water, including the following steps: (5) Adsorption experiments were carried out in 200 mL of pyrene solution with an initial concentration of 0.025 mg / L. The experimental results are as follows: Fig.15 .H 3 PO 4 The activated carbon has a pyrene removal rate of about 93.40%, and the equilibrium adsorption capacity is about 0.92862 mg / g. Fig.19 After adsorption of pyrene, H 3 PO 4 FTIR of the activated adsorbent. As shown in the figure, the peaks at 3436, 2346, 1737 and 648 cm -1 The peak at 100 nm and the peak intensity corresponded to the stretching vibration of CH after adsorption of pollutants. Compared with the standard FTIR spectrum of pyrene in the ChemSider database, it was found that the standard spectrum could correspond to the enhanced peak of a specific wavelength on the adsorbent, which could provide evidence for the presence of pyrene on the adsorbent.
[0049] (6) Recover the adsorbent after adsorption equilibrium. The adsorbent used to adsorb the pyrene solution was freeze-dried at -80°C, soaked in 10 mL of methanol and placed in a shaker for 2 h. The solid and liquid were then separated, and the recovered adsorbent was washed with water and dried for re-adsorption. The recovered adsorbent was used for re-adsorption of pyrene pollutants, and the adsorption efficiency was maintained at more than 75%. The washed methanol was concentrated by nitrogen blowing and then separated to maintain a good pyrene recovery rate.
[0050] Comparative Example 1 This comparative example is based on the aforementioned Example 1, and adopts the conditions and steps basically the same as those in Example 1 to prepare the modified carbon-based adsorbent, the only difference being that the time of magnetic stirring activation in step (2) is 6 hours.
[0051] The SEM images of the modified carbon-based adsorbent material prepared in this example are as follows: Figure 4 As shown, through H 3 PO 4The surface microstructure and physical and chemical properties of activated carbon materials activated for 6 hours are similar to those of Figure 2 The difference is big, its outer surface is still relatively smooth, but compared to Fig.10 , part of the gully-like mesoporous structure has been added. After testing, it does not have the microstructure and physical and chemical properties of the modified carbon-based adsorbent material prepared in Example 1. It can be seen that when the activation time is insufficient, the modified carbon-based adsorbent material with the technical characteristics and effects of Example 1 cannot be obtained.
[0052] Comparative Example 2 This comparative example is based on the aforementioned Example 1, and adopts the conditions and steps basically the same as those in Example 1 to prepare the modified carbon-based adsorbent, the only difference being that the time of magnetic stirring activation in step (2) is 24 hours.
[0053] The SEM images of the modified carbon-based adsorbent material prepared in this example are as follows: Figure 5 As shown, through H 3 PO 4 The surface microstructure and physical and chemical properties of activated carbon materials activated for 24 hours are similar to those of Figure 2 There is a big difference. As the activation time increases, the carbon in the activated carbon will completely react with the activator, resulting in serious surface fragmentation of the material. No stable, discretely distributed, and interconnected gullies and groove-shaped mesoporous structures are formed inside and outside. After testing, it does not have the microstructure and physical and chemical properties of the modified carbon-based adsorbent material prepared in Example 1. It can be seen that when the activation time is too long, it is impossible to obtain a modified carbon-based adsorbent material with the technical characteristics and effects of Example 1.
[0054] Comprehensive observation Figure 2-Figure 5 From the continuous activation time axis, it can be seen that when other activation conditions remain unchanged, the microstructure and physicochemical properties of the modified adsorbent material change with the activation time. When the activation time is 6 h, only a few slits and holes appear on its surface (such as Figure 4 As shown in the figure, it does not meet the requirements; as the activation time increases, the number of slits and holes gradually increases, and the microporous structure gradually collapses into mesoporous and macroporous structures. When the activation time is 10-14 hours, it just meets the requirements (as shown in the figure). Figure 2 If the activation time exceeds 10-14 hours and lasts for 24 hours, the surface structure of the adsorbent will be severely broken (as shown in Figure 5 As shown in the figure, the material performance cannot meet the requirements; therefore, when other activation conditions remain unchanged, only activation for 10 to 14 hours can meet the performance requirements.
[0055] The following Examples 4 to 6, as well as Comparative Examples 3 and 4, all use ZnCl 2 They are activators, and the difference lies in the different process conditions used in the activation process.
[0056] Example 4 This example is based on the above-mentioned Example 1, and the modified carbon-based adsorbent is prepared using substantially the same conditions and steps as Example 1. The only difference is that the activator used in this example is ZnCl 2 The mass ratio of the pretreated high-density activated carbon material to the activator dry matter is 1:3.5.
[0057] In this embodiment, ZnCl 2 The modified carbon-based adsorbent prepared by activation for 12 h, the proportion of each element and the pore structure parameters are shown in Table 1; the SEM image is shown in Figure 6 As shown, it can be seen that there are a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and a small number of discrete irregular groove-shaped mesopores as auxiliary nano-micrometer multi-scale modified carbon-based adsorbent particles, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.0~4.5μm (see Figure 7 ).
[0058] In addition, the adsorbent material prepared in this embodiment has 3752, 3615, 1765, 1130, 1012 and 987 cm -1 The peaks at 3752 and 3615 cm-1 correspond to OH, C=C bond, carboxyl O=CO bond, CH in-plane bending vibration, alkoxy CO and CH out-of-plane bending vibration. Compared with the unmodified activated carbon, the -OH stretching vibration intensity at 3752 and 3615 cm-1 is significantly enhanced, and the wavelength at 1545 cm-1 is the C=C stretching vibration of the benzene ring in the carbon-based adsorbent material.
[0059] Finally, the ZnCl prepared in this example 2 Modified carbon-based adsorbents were used to adsorb and recover naphthalene from water. Fig.13 As shown in the figure, the adsorption amount gradually increases with the increase of time. In 200mL naphthalene solution with an initial concentration of 30 mg / L within 30min, the adsorption capacity of the adsorbent reaches equilibrium. 2 The activated carbon adsorbent has a naphthalene removal rate of about 96.57% and an equilibrium adsorption capacity of about 98.87 mg / g. Fig.17 After adsorption of naphthalene, ZnCl 2 FTIR of the activated adsorbent. As shown in the figure, the peaks at 3752, 3615, 1746, 1517 and 1012 cm -1The peak intensity at 2338 cm-1 is stronger than that at 2347 cm-2. Compared with the standard FTIR spectrum of naphthalene in the ChemSider database, it is found that the standard spectrum can correspond to the enhanced peaks of specific wavelengths on the adsorbent, which can provide evidence for the presence of naphthalene on the adsorbent. After adsorption, the peaks corresponding to the vibration of the C=C bond skeleton increase from 2338 cm-1 to 2347 cm-1. -1 Move to 2362 cm -1 , which confirms that π-π interaction plays an important role in the adsorption process between the adsorbent and PAHs.
[0060] Finally, the prepared modified carbon-based adsorbent is applied to the adsorption and recovery of phenanthrene in water, including the following steps: (5) If Fig.14 As shown in the figure, the adsorption amount of phenanthrene gradually increases with time. In 200 mL of phenanthrene solution with an initial concentration of 1 mg / L within 30 min, the adsorption capacity of the adsorbent reaches equilibrium. 2 The activated carbon has a phenanthrene removal rate of 99.33%, and the equilibrium adsorption capacity is approximately 9.529 mg / g. Fig.18 ZnCl after adsorption of phenanthrene 2 FTIR of the activated adsorbent. As shown in the figure, the peaks at 3744, 1540 and 698 cm -1 There is a peak at 698 cm -1 The peak intensity corresponds to the stretching vibration of CH after adsorption of pollutants. Compared with the standard FTIR spectrum of phenanthrene in the ChemSider database, it is found that the standard spectrum can correspond to the enhanced peak of a specific wavelength on the adsorbent, which can provide evidence for the presence of phenanthrene on the adsorbent.
[0061] Example 5 This example is based on the above-mentioned Example 2, and the modified carbon-based adsorbent is prepared using substantially the same conditions and steps as Example 2. The only difference is that the activator used in this example is ZnCl 2 The mass ratio of the pretreated high-density activated carbon material to the activator dry matter is 1:7.
[0062] Finally, the prepared modified carbon-based adsorbent is applied to the adsorption and recovery of pyrene in water, including the following steps: (5) Experimental results are as follows Fig.15 As shown. ZnCl 2 The activated carbon has a pyrene removal rate of about 85.52%, and the equilibrium adsorption capacity is about 0.8868 mg / g. Fig.19 After adsorption of pyrene, ZnCl 2 FTIR of the activated adsorbent. As shown in the figure, the peaks at 3436, 1737 and 648 cm -1Compared with the standard FTIR spectrum of pyrene in the ChemSider database, it is found that the standard spectrum can correspond to the enhanced peak of a specific wavelength on the adsorbent, which can provide evidence for the presence of pyrene on the adsorbent.
[0063] (6) Recover the adsorbent after adsorption equilibrium. The adsorbent used to adsorb the pyrene solution was freeze-dried at -80°C, soaked in 10 mL of methanol and placed in a shaker for 2 h. The solid and liquid were then separated, and the recovered adsorbent was washed with water and dried for re-adsorption. The recovered adsorbent was used for re-adsorption of pyrene pollutants, and the adsorption efficiency was maintained at more than 75%. The washed methanol was concentrated by nitrogen blowing and then separated to maintain a good pyrene recovery rate.
[0064] Example 6 This example is based on the above-mentioned Example 3, and adopts the same conditions and steps as Example 1 to prepare the modified carbon-based adsorbent. The only difference is that the activator used in this example is ZnCl 2 The mass ratio of the pretreated high-density activated carbon material to the activator dry matter is 1:5.5.
[0065] The microstructure and physicochemical properties of the modified carbon-based adsorbents prepared in Example 5 and Example 6 were observed and tested, respectively, and it was found that they were highly similar to the modified carbon-based adsorbent prepared in Example 4, so they will not be described again.
[0066] Comparative Example 3 This comparative example is based on the aforementioned Example 4, and adopts the conditions and steps basically the same as those of Example 4 to prepare the modified carbon-based adsorbent, the only difference being that the time of magnetic stirring activation in step (2) is 6 hours.
[0067] The SEM image of the modified carbon-based adsorbent prepared in this example is as follows: Figure 8 As shown, only a small amount of grooves and concave mesopores are formed on the surface and inside of the material, and the surface is still relatively smooth as a whole. After testing, the microstructure and physical and chemical properties of the adsorbent prepared in Example 4 are greatly different.
[0068] Comparative Example 4 This comparative example is based on the aforementioned Example 4, and adopts the conditions and steps basically the same as those of Example 4 to prepare the modified carbon-based adsorbent, the only difference being that the time of magnetic stirring activation in step (2) is 12 hours.
[0069] The SEM images of the modified carbon-based adsorbent prepared in this example are as follows: Fig. 9As shown, the surface and interior of the material are severely broken, and it is impossible to form structurally stable grooves and groove-shaped mesopores. After testing, the microstructure and physical and chemical properties of the adsorbent prepared in Example 4 are greatly different.
[0070] Comprehensive observation Figure 6-Figure 9 From the activation time axis (continuous activation), it can be seen that when other activation conditions remain unchanged, the microstructure and physicochemical properties of the modified adsorbent material change with the activation time. When the activation time is 6 h, only a few slits and holes appear on its surface (such as Figure 8 As shown in the figure, it cannot meet the requirements. As the activation time increases, the number of slits and holes increases, and the microporous structure gradually collapses into mesoporous and macroporous structures. When the activation time reaches 10-14 hours, it can just meet the requirements ( Figure 6 If the activation lasts for 24 hours after 10-14 hours, the surface structure of the adsorbent will be severely broken (such as Fig. 9 As shown in the figure, the material performance cannot meet the requirements; therefore, only the material activated for 10 to 14 hours can meet the requirements.
[0071] Comparative Example 5 See attached Figures 10 to 19 In this comparative example, high-density activated carbon (AC) is not modified and is directly used as an adsorbent to conduct adsorption and desorption tests of polycyclic aromatic hydrocarbons, an organic pollutant in water. The specific contents include the following: 1. Preparation of unmodified carbon-based adsorbent (1) Wash the commercially available high-density activated carbon material with deionized water three times to remove surface impurities; (2) Place the above adsorbent in a drying device and dry it at 60°C for 12 h, then seal it for later use.
[0072] 2. Material characterization of modified activated carbon Field emission scanning electron microscopy (SEM, Gemini SEM 500) was used to analyze the surface morphology of the adsorbed materials. A multi-station extended automatic rapid surface area analyzer (Micromeritics ASAP 2020) was used to analyze the surface morphology of the adsorbed materials at 77 K. 2 BET (Bet-E) was used to characterize the total surface area, total pore volume, and micropore volume of the material. FTIR (Fourier transform infrared spectroscopy) was used to test the surface functional groups. Fig.10 The SEM image of AC material shows that the original activated carbon surface is relatively smooth, with fewer pores and no grooves on the surface, which is not conducive to the attachment of large-sized PAHs on its surface. Table 1 shows the proportion of elements C, N and O in the adsorbent, with the C element being the highest at 95.18%. The parameters of AC are shown in Table 1. The specific surface area of the unmodified adsorbent is 164.9 cm 2 ·g-1 , which is lower than that of the modified adsorbent, and is mainly composed of micropore structures below 2 nm.
[0073] (III) Effect of unmodified activated carbon on naphthalene remediation in water (1) The commercially available high-density activated carbon material was washed with deionized water three times to remove surface impurities. Subsequently, it was placed in a drying device and dried at 60°C for 12 h and sealed for later use.
[0074] (2) Weigh 5 mg of the activated carbon obtained above to conduct a naphthalene adsorption experiment in 200 mL of naphthalene solution with an initial concentration of 30 mg / L. The experimental results are as follows: Fig.13 The removal rate of naphthalene by unmodified activated carbon was about 43.38%, and the equilibrium adsorption capacity was about 66.15 mg / g.
[0075] (IV) Effect of unmodified activated carbon on the remediation of phenanthrene in water (1) The commercially available high-density activated carbon material was washed with deionized water three times to remove surface impurities. Subsequently, it was placed in a drying device and dried at 60°C for 12 h and sealed for later use.
[0076] (2) Weigh 5 mg of the activated carbon obtained above to conduct a phenanthrene adsorption experiment in 200 mL of phenanthrene solution with an initial concentration of 1 mg / L. The experimental results are as follows: Fig.14 The removal rate of phenanthrene by unmodified activated carbon is about 38%, and the equilibrium adsorption capacity is about 6.206 mg / g.
[0077] (V) Effect of unmodified activated carbon on the remediation of pyrene in water (1) The commercially available high-density activated carbon material was washed with deionized water three times to remove surface impurities. Subsequently, it was placed in a drying device and dried at 60°C for 12 h and sealed for later use.
[0078] (2) Weigh 5 mg of the activated carbon obtained above to conduct a pyrene adsorption experiment in 200 mL of pyrene solution with an initial concentration of 0.025 mg / L. The experimental results are as follows: Fig.15 The removal rate of pyrene by unmodified activated carbon was about 26.95%, and the equilibrium adsorption capacity was about 0.2531 mg / g.
[0079] (VI) Infrared spectra of adsorbent before and after adsorption Weigh 5 mg of the unmodified activated carbon obtained above and conduct adsorption experiments in 200 mL of naphthalene, phenanthrene and pyrene solutions. After adsorption, centrifuge and collect the precipitate and freeze-dry it at -80 °C for 24 h; then use Fourier transform infrared spectrometer (FTIR, Bruker tensor 27) to analyze the functional groups in the adsorbent before and after adsorption. The results are as follows: Fig.16Compared with the modified adsorbent prepared in Example 1, the surface functional group composition and content of the unmodified adsorbent are less. Significant benzene ring C=C stretching vibration and CH in-plane bending vibration peaks appear at wavelengths of 1545 and 1130 cm-1, respectively. Figure 17-19 This is the FTIR of the unmodified adsorbent after adsorption of naphthalene, phenanthrene and pyrene. Compared with the standard FTIR spectra of naphthalene, phenanthrene and pyrene in the ChemSider database, it is found that the peaks appearing in the standard spectra are weaker or do not appear at the wavelength of the adsorbent after adsorption. This shows that the π-π interaction or chemical adsorption of unmodified activated carbon is difficult to play a role in the removal of PAHs, and the removal of PAHs in aqueous solution mainly relies on the micropore filling effect.
[0080] The modified carbon-based adsorbent prepared by the above-mentioned embodiments of the present invention enriches the oxygen-containing functional groups of the material after activation, and has a large number of gully-shaped mesoporous structures and surface groove-shaped mesoporous structures; by utilizing the high delocalization performance of gullies and grooves, and synergistically interacting through π-π, it can significantly improve the attachment of PAHs and the like on the adsorbent material, promote the rapid enrichment of pollutants on the surface, and also facilitate rapid desorption. After actual testing, the adsorbent can achieve a removal rate of more than 90% for naphthalene, phenanthrene and pyrene, and the maximum adsorption capacity can reach 199.9 mg / g, which can be used to treat wastewater containing naphthalene, phenanthrene and pyrene; the adsorbent material after adsorption can be further dissolved in methanol / acetonitrile, purified and realized The recovery of PAHs and the regeneration of the adsorbent. The invention utilizes the combination of the mesoporous structure of the gullies and grooves that interpenetrate each other in the modified carbon-based adsorbent. On the one hand, it accelerates the adsorption of pollutants, increases the load, and reduces the amount of adsorbent, while supporting the rapid desorption and recovery of PAHs on the adsorbent. The present invention is of great significance to the resource utilization and reduction of wastewater from coal chemical, petroleum and coking enterprises, has broad application prospects in the fields of organic wastewater treatment and pollutant recovery, and can meet the needs of large-scale, industrialized promotion and popularization.
[0081] It should be noted that in other embodiments of the present invention, within the scope of the steps, components, ratios, process parameters and conditions recorded in the present invention, other different schemes obtained by specific selection can achieve the technical effects recorded in the present invention, so the present invention will no longer list them one by one.
[0082] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. All equivalent changes made according to the components, proportions and processes of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water, characterized in that: The steps include: S1. Preparation of modified carbon-based adsorbent The pretreated high-density activated carbon is added to an activator solution, and the concentration, temperature, stirring speed and stirring time of the activator solution are synchronously controlled, and the activation is performed by continuous magnetic stirring, so as to obtain nano-micron multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and supplemented by a small number of discrete irregular groove-shaped mesopores; the activator is H3PO4 or ZnCl2; S2. Treatment of wastewater polluted by polycyclic aromatic hydrocarbons The prepared modified carbon-based adsorbent particles are added to wastewater containing polycyclic aromatic hydrocarbons for adsorption treatment to fully enrich the polycyclic aromatic hydrocarbons in the water body; S3. Recovery of PAHs The modified carbon-based adsorbent enriched with polycyclic aromatic hydrocarbons is desorbed by dissolving, and then the solid-liquid separation is performed to recover the modified carbon-based adsorbent and the supernatant respectively; the recovered carbon-based adsorbent is washed with water and dried to restore the adsorption capacity; the supernatant is quickly concentrated, separated, purified, and the polycyclic aromatic hydrocarbons are extracted.
2. The method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water as claimed in claim 1, wherein step S1 specifically comprises the following steps: S1-1 Wash the high-density activated carbon with deionized water to remove surface impurities; then dry it in a drying device to obtain pretreated high-density activated carbon; S1-2 synchronously controls the concentration, temperature, stirring speed and stirring time of the activator solution including: According to the mass ratio of H3PO4 to pretreated high-density activated carbon of 1: (5-10), or the mass ratio of ZnCl2 to pretreated high-density activated carbon of 1: (3.5-7), the pretreated high-density activated carbon is added to the solution of 0.1-0.2 mol / L prepared by the above activator, and activated by magnetic stirring at a speed of 450-550 rpm for 10-14 h at a temperature of 25-40°C, so that the activator reacts with the carbon matrix in the activated carbon, removes insoluble impurities and changes the microscopic surface morphology and physicochemical properties of the activated carbon, and obtains nano-micron multi-scale modified carbon-based adsorbent particles mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and a small number of discrete irregular groove-shaped mesopores as auxiliary, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5-4.5 μm; S1-3: washing the modified carbon-based adsorbent particles activated in step S1-2 with deionized water until the pH of the rinse solution is approximately neutral, and collecting the activated modified carbon-based adsorbent particles by centrifugation; S1-4 The modified activated carbon particles obtained in step S1-3 are placed in a vacuum drying oven for drying, cooled to room temperature, collected and placed in a glass desiccator for standby use, to obtain a modified carbon-based adsorbent.
3. The method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water as claimed in claim 2, characterized in that: The high-density activated carbon in step S1-1 is an activated carbon granular material taken out from a commercially available industrial air filter protective mask; In step S1-2, the concentration, temperature, stirring speed and stirring time of the activator solution are synchronously controlled as follows: the solution concentration is 0.1 mol / L, the temperature is 30°C, the rotation speed is 500 rpm, and the magnetic stirring is carried out for 12 hours to allow the activator to react with the carbon matrix in the activated carbon, so as to obtain nano-micrometer-scale multi-scale modified carbon-based adsorbent particles with more interconnected and nearly parallel long strip-shaped slit mesopores as the main part and fewer discrete irregular groove-shaped mesopores as the auxiliary part, and the slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.75~4.5μm.
4. The method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water according to claim 1, characterized in that: The step S2 specifically includes the following steps: S2-1: Detection of concentration of PAHs in water; S2-2: Calculate the required amount of carbon-based adsorbent; S2-3: Add carbon-based adsorbent to wastewater, stir, and take samples at specific time intervals; S2-4: Detect the residual concentration of PAHs in the treated water. If it is not reached, continue stirring and treating until it meets the set emission standards.
5. The method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water according to claim 1, characterized in that: The step S3 specifically includes the following steps: S3-1: Desorbing the modified carbon-based adsorbent enriched with polycyclic aromatic hydrocarbons by dissolving it in methanol or acetonitrile, followed by solid-liquid separation, and recovering the modified carbon-based adsorbent and the supernatant respectively; S3-2: Wash and dry the recovered carbon-based adsorbent to restore its adsorption capacity for the next adsorption; S3-3: Use extraction, rotary evaporation or nitrogen blowing to quickly concentrate the supernatant, separate, purify and extract polycyclic aromatic hydrocarbons.
6. A modified carbon-based adsorbent, characterized in that: It is prepared by step S1 described in any one of claims 1 to 3, with high-density activated carbon as the substrate, and the activation reaction conditions of the activator are synchronously controlled to obtain a surface-modified solid particle material after controlled activation. It is used to implement the method for rapid and efficient removal and recovery of polycyclic aromatic hydrocarbons in water bodies described in any one of claims 1 to 5.
7. The modified carbon-based adsorbent according to claim 6, characterized in that: The surface of the modified carbon-based adsorbent has a nano-micrometer multi-scale microstructure, which is mainly composed of a large number of long strip-shaped slit mesopores that are interconnected and distributed in a nearly parallel direction, and supplemented by a small number of discrete irregular groove-shaped mesopores. The slit height of the long strip-shaped slit mesopores and the diameter of each irregular groove-shaped mesopore are mainly distributed in the range of 1.5 to 4.5 μm, and can quickly adsorb and analyze polycyclic aromatic hydrocarbons of different molecular weights.
Citation Information
Patent Citations
Mesoporous activated carbon and methods of producing same
CN103140442A
Preparation method for improving specific surface area of sunflower disc biochar, and method for adsorbing polycyclic aromatic hydrocarbon by using sunflower disc biochar
CN113926425A
Cited By
Device and method for recovering aromatic hydrocarbon in washing water of methanol-to-aromatic hydrocarbon process
CN121405321A
An apparatus and method for recovering aromatics from washing water in a methanol-to-aromatics process.
CN121405321B